The Distinctive Characteristics of Commercial and Investment Arbitration Proceedings: Lex multiplex, universa curiositas, ius unum? (Polish Yearbook of International Law, 2016)
The thrust of this article is to examine a contemporary international arbitration process in commercial and investment cases, specifically the interplay of common law and civil law elements in the taking of evidence. It begins with a survey of the provisions of the most popular international arbitration instruments, including international arbitration rules and IBA Rules on the Taking of Evidence in International Arbitration. Following the discussion of some relevant examples of international arbitration instruments, the author tries to answer the question whether these instruments, in their current form, support the popular thesis that the international arbitration process has become largely harmonized. In trying to verify this thesis, the article also goes beyond the text of international arbitration instruments and considers the influence of the cultural biases of international arbitration actors.